Fenomena Kecanduan Gadget pada Mahasiswa Farmasi di Lingkungan Universitas Muhammadiyah Makassar - Magfira Ramadhani; Andi Nur Kamilah Maritza; Jumriana; Diva Maulia Mahyar (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
This study aims to identify the phenomenon of gadget addiction among Pharmacy students at Muhammadiyah University Makassar through a qualitative literature review. Excessive gadget use has become a global issue, with students often being particularly vulnerable due to academic demands and easy access to technology. The research methodology employed is qualitative literature review, encompassing various sources such as scientific journals, books, and research reports on gadget addiction and its impact on students. Literature analysis involved identifying key themes emerging from the reviewed sources. Findings indicate that gadget addiction can affect various aspects of students' lives, including reduced study concentration, poor sleep quality, and decreased face-to-face social interaction. Additionally, the study found a correlation between gadget addiction and increased levels of stress and anxiety among students. The study concludes that gadget addiction is a significant phenomenon among Pharmacy students and underscores the importance of university interventions to mitigate its negative effects. Recommendations include education on healthy gadget use and provision of psychological support for students.